Volatility criteria of isomerate-enriched gasoline-ethanol blends - Manal Amine; Ezis N. Awad; Y. Barakat (Egyptian Journal of Petroleum)
In this study, four isomerate-enriched gasolines were formulated from the local refinery streams of Cairo Petroleum Refinery Co., Egypt. Each of these isomerate-enriched hydrocarbon gasolines were mixed with 10 vol% of anhydrous ethanol. Distillation data were collected for the eight formulated fuels using the standard ASTM-D86 distillation method. From these data, eight distillation profiles were constructed and subsequently eight distillation profiles equations, were developed. From these equations, areas under distillation curves for the hydrocarbon gasolines (AUDC)G and those for ethanol blended ones (AUDC)G-10E were estimated using calculus definite integration method. Accordingly, area due to azeotrope formation (ADAF) for each ethanol-blended fuel was calculated (AUDCG-AUDCG-10E). Also, vapor pressure, T(v/l) = 20, T50 and deriveability index (DI) of the fuel samples were studied. The results confirm that the volatility of all fuel formulations considerably increases with addition of 10 vol% ethanol while it slightly increases with the slight increase in the isomerate content.